Widespread theta synchrony and high-frequency desynchronization underlies enhanced cognition. Issue 1 (December 2017) - Solomon, E.; Kragel, J.; Sperling, M.; Sharan, A.; Worrell, G.; Kucewicz, M.; Inman, C.; Lega, B.; Davis, K.; Stein, J.; Jobst, B.; Zaghloul, K.; et al.
Abstract The idea that synchronous neural activity underlies cognition has driven an extensive body of research in human and animal neuroscience. Yet, insufficient data on intracranial electrical connectivity has precluded a direct test of this hypothesis in a whole-brain setting. Through the lens of memory encoding and retrieval processes, we construct whole-brain connectivity maps of fast gamma (30–100 Hz) and slow theta (3–8 Hz) spectral neural activity, based on data from 294 neurosurgical patients fitted with indwelling electrodes. Here we report that gamma networks desynchronize and theta networks synchronize during encoding and retrieval. Furthermore, for nearly all brain regions we studied, gamma power rises as that region desynchronizes with gamma activity elsewhere in the brain, establishing gamma as a largely asynchronous phenomenon. The abundant phenomenon of theta synchrony is positively correlated with a brain region's gamma power, suggesting a predominant low-frequency mechanism for inter-regional communication. Synchronous neural activity is related with memory encoding and retrieval, but it is not clear whether this happens across the whole brain. Here, authors use intracranial recordings to show that gamma networks are largely asynchronous, desynchronizing while theta synchronizes during memory encoding and retrieval.